2010
DOI: 10.1002/pc.20892
|View full text |Cite
|
Sign up to set email alerts
|

Nonisothermal crystallization kinetics of poly(ethylene terephthalate)/clay nanocomposites prepared by melt processing

Abstract: In this study, cold and melt crystallization behaviors of amorphous poly(ethylene terephthalate) (PET)/clay nanocomposites were investigated. Two nanocomposite samples with the same amount of inorganic content were prepared by melt processing using natural montmorillonite (Na‐MMT) and organo‐modified montmorillonite (org‐MMT). Depending on the clay structure, clay dispersion into PET and crystallization behavior of the samples were studied using X‐ray diffraction and differential scanning calorimetry methods, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…Crystallization studies are crucial in understanding the macroscopic properties of nanocomposites (vide infra) given that inclusion of inorganic particles in polymeric matrices can induce diverse effects such as heterogeneous nucleation [31,32], suppression of crystal growth [33], and preferential development of a certain crystalline phase at the expense of other phases [34,35]. In agreement with previous studies on PET/clay systems [26,27,36] the DSC curves shown in Fig. 4 reveal the nucleating effect of MMT-SPE and MMT-MSIm clays as evident by the higher crystallization temperature (T cr ) observed for the nanocomposites compared to the neat matrix (cooling run in Fig.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Crystallization studies are crucial in understanding the macroscopic properties of nanocomposites (vide infra) given that inclusion of inorganic particles in polymeric matrices can induce diverse effects such as heterogeneous nucleation [31,32], suppression of crystal growth [33], and preferential development of a certain crystalline phase at the expense of other phases [34,35]. In agreement with previous studies on PET/clay systems [26,27,36] the DSC curves shown in Fig. 4 reveal the nucleating effect of MMT-SPE and MMT-MSIm clays as evident by the higher crystallization temperature (T cr ) observed for the nanocomposites compared to the neat matrix (cooling run in Fig.…”
Section: Resultssupporting
confidence: 73%
“…4 reveal the nucleating effect of MMT-SPE and MMT-MSIm clays as evident by the higher crystallization temperature (T cr ) observed for the nanocomposites compared to the neat matrix (cooling run in Fig. 4) and the position of the cold crystallization exotherms observed in the first heating run [36].…”
Section: Resultsmentioning
confidence: 99%
“…All plots show a linear relationship between ln α and ln t, indicating that the combined Avrami and Ozawa equations could well describe the crystallization behaviour of MDPE and PECN15. Liu equation has been also successfully used to define the crystallization kinetics for alumina-filled poly(ether ether ketone)(Kuo et al 2006), polyethyleneorganic-montmorillonite NCs(Xu et al 2005), nylone 6-graphite NCs(Weng et al 2003), nylone 6-attapulgite NCs(Shi et al 2010) and polyethyleneterephhthalate-clay NCs(Durmus et al 2010).…”
mentioning
confidence: 99%
“…There have been many studies on melt processing methods to synthesize PET/ nanoclay nanocomposites (Ghasemi et al, 2011;Durmus et al, 2010;Wu et al, 2013Wu et al, , 2014Kim et al, 2013a;Ghanbari et al, 2013b;Gokkurt et al, 2013). Melt-blended PET nanocomposites have been made with different nanoclays such as montmorillonite (MMT), hectorite, and magadiite (Costache et al, 2006).…”
Section: Synthesis Methodsmentioning
confidence: 99%